RANCANG BANGUN PROTOTYPE DISPLAY ANTRIAN PELANGGAN MENGGUNAKAN TEKS DAN SUARA BERBASIS INTRANET - Heru Yulianto; Darmanto Darmanto (Lembaga Pengembangan Kinerja Dosen, 2022)
The development of information technology in various fields, one of which is in the field of queuing systems. That we know about the queuing system which is so tedious because of the long process of queuing. Therefore, the number of customer queues at several banks so that customers cannot relax to carry out transactions at the bank is a problem that is often encountered, as well as what happened at PT. BPR SARIBUMI Bank Godong Branch which still uses a manual system. To overcome this problem, a queue display is used that uses text and voice displays and prints the queue serial number so that customers no longer need to queue conventionally. With this queuing system, the queue counter clerk, cashier or teller will have no difficulty in determining the first person to be served in the queue. This is a solution, but the display of the queue display uses electronic equipment that performs a counter so that the possibility of damage to the device exists. In making this final project the author uses Microsoft Visual Basic 6.0 software and MySQL database.